Когнітивне моделювання впливу інформатизації на соціально-економічні показники регіону - Gorelova, Galina; Magomedova, Sabina; Feilamazova, Svetlana (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2021)
The article discusses topical issues of the influence of informatization on the development of the country’s regions in the conditions of the modern unstable world. The nature of the development of a region can be reflected and understood on the basis of qualitative and quantitative information about its socio-economic indicators, about their relationship and trends in their changes under the influence of internal and external factors. At the same time, information can most often be incomplete, difficult to access, untimely, contradictory, etc. Therefore, in this paper, it is proposed to use a cognitive approach and cognitive modeling of complex systems to overcome the problems of information deficiency by imitating cognitive modeling of the structure and behavior of a complex regional system. The simulation was carried out using the author’s CMCS (Cognitive Modeling Complex System) software system. The results of multi-stage cognitive modeling, consisting in the development of cognitive maps “Influence of ICT on the state of the region” and “Digitalization of the republic” (according to the socio-economic state of the Republic of Dagestan), analysis of structural properties and modeling scenarios for the development of situations on the model are presented. Scenarios make it possible to foresee the ways of possible development of the system under the influence of various factors, including the factor of informatization.